Intravenous thrombolysis for acute ischemic stroke occurring during hospitalization for transient ischemic attack - Tsivgoulis, Georgios; Sharma, Vijay K; Mikulik, Robert; Krogias, Christos; Haršány, Michal; Bavarsad Shahripour, Reza; Athanasiadis, Dimitrios; Teoh, Hock Luen; Piperidou, Charitomeni; Alexandrov, Andrei V (International journal of stroke, 2014)
BACKGROUND: There are limited data regarding the use of intravenous thrombolysis in patients who experienced acute ischemic symptoms during their hospitalization for prior transient ischemic attack. AIM: We sought to prospectively evaluate the safety and efficacy of intravenous thrombolysis for the treatment of acute ischemic stroke occurring during hospitalization for transient ischemic attack in an international, multicenter study. METHODS: Consecutive patients with acute ischemic stroke that occurred during hospitalization for prior transient ischemic attack were treated with intravenous thrombolysis in five tertiary-care stroke centers. Early arterial recanalization was determined by transcranial Doppler at the end of recombinant tissue plasminogen activator infusion using previously validated criteria. Symptomatic intracranial hemorrhage complicating intravenous thrombolysis was evaluated using the National Institute of Neurological Disorders and Stroke Recombinant Tissue Plasminogen Activator Stroke Study definition. Functional independence at three-months was defined as Modified Rankin Scale score of 0-2. RESULTS: Systemic recombinant tissue plasminogen activator infusion (median onset-to-treatment time 70 mins, interquartile range 50-150) was given in 25 consecutive patients (mean age 66 ± 10 years) who developed acute ischemic stroke symptoms (median National Institutes of Health Stroke Scale score 10 points; interquartile range 8-14) during hospitalization for prior transient ischemic attack (median ABCD(2) score 5 points; median time-to-symptom recurrence 24 h, interquartile range 24-48). No symptomatic intracranial hemorrhage (0%; 95% confidence interval 0-12%) was documented. Early complete recanalization occurred in 64% of patients (95% confidence interval 44-80%), and 84% (95% confidence interval 65-94%) achieved three-month functional independence. The rate of three-month functional independence was higher in patients treated with intravenous tissue plasminogen activator within 90 mins from symptom onset compared with those with onset-to-treatment time>90 mins (81% vs. 33%; P = 0.031). CONCLUSIONS: Intravenous thrombolysis for symptoms of acute ischemic stroke occurring after hospitalization for transient ischemic attack appears to be safe. These pilot data support resetting the clock if new symptoms recur shortly after transient ischemic attack.
Keywords: Hemorrhage; neparametrická statistika; neurozobrazování; Humans; lidé středního věku; tranzitorní ischemická ataka; Ultrasonography, Doppler, Transcranial; Stroke; intravenous thrombolysis; transient ischemic attack; Female; Aged; výsledek terapie; senioři; lidé; Tissue Plasminogen Activator; mezinárodní spolupráce; hospitalizace; intravenózní podání; Ischemic Attack, Transient; časové faktory; International Cooperation; fibrinolytika; cévní mozková příhoda; Fibrinolytic Agents; ženské pohlaví; Hospitalization; Male; tkáňový aktivátor plazminogenu; Middle Aged; Treatment Outcome; Statistics, Nonparametric; krvácení; mužské pohlaví; prospektivní studie; Administration, Intravenous; ultrasonografie dopplerovská transkraniální; Time Factors; acute ischemic stroke; Neuroimaging; Prospective Studies